REDESAIN RAKEL DAN PEMBERIAN PEREGANGAN AKTIF MENURUNKAN BEBAN KERJA DAN KELUHAN MUSKULOSKELETAL SERTA MENINGKATKAN PRODUKTIVITAS KERJA PEKERJA SABLON PADA INDUSTRI SABLON SURYA BALI DI DENPASAR - ., Daryono .; Sutjana, I Dewa Putu; Muliarta, I Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 2 (2016): Volume 2 No 2 Desember 2016, 2016)
Problems ergonomics in industrial screen printing traditional fabrics such as work attitude unnatural causing musculoskeletal disorders in workers printing. To overcome these problems, especially for fabric printing activity done by redesigning Rakel research and giving active stretching. The purpose of this study was to know the effects of the using redesigning Rakel and active stretching for the fabric screen printing workers to decrease the workload, musculoskeletal disorders and increased work productivity. The study design is the design of the same subject, involving 12 workers printing male, 20-45 years old, between 1-5 years of work experience. Research into two phases. The first phase (I) subjects treated with Rakel without redesigning work and without giving active stretching. The second phase (II) subjects treated with redesigning work Rakel and giving active stretching. Among the two phases of the study, given a wash out period for 2 days and adaptation redesigning Rakel for 4 days, to eliminate carry-over effects. The workload is measured by the method of pulse 10 beats, musculoskeletal complaints measured by a questionnaire Nordic Body Map at 4 Likert scale and work productivity based on the ratio between output and input. Data were analyzed with the Shapiro-Wilk test to determine the normality of the data, paired t-test to test the significance difference variable workload and productivity of work at the significance level ? = 0.05 and Wilcoxon test for variables musculoskeletal complaints. The results showed that redesigning Rakel and provision of active stretching can reduce the workload of 30,3% (p<0.05) and lower musculoskeletal complaints by 16,9% (p<0.05) as well as increasing work productivity by 45,5% (p <0.05). It concluded that the redesign Rakel and provision of active stretching can reduce the workload and musculoskeletal disorders and increase productivity for workers printing. Suggested to the owner of a similar business industry to make good working conditions referring to ergonomic principles, so as to create safer working conditions, comfortable, healthy and productive workers.
Keywords: Redesign Rakel, Active Stretching, Workload Complaints, Work Productivity